Barium Magnesium Hydrogen Phosphate Single Crystal Growth in Silica Gel Medium: Characterization Studies and Laser Irradiated Nucleation Reduction Process Strategy - SUNDARAMOORTHI, P.; KALAINATHAN, S.; SHAJITHA BANU, A. (Asian Journal of Chemistry, 2010)
In the chemical reaction method, barium magnesium hydrogen phosphate (BMHP) crystals are grown in silica gel medium using different gel densities and various concentrations of orthoposphoric acid and supernatant solutions. The gel pH gives an important role in the formation of different H3PO4 species in the phosphoric system, the pH range in which HPO42- ions dominates were considered, which in turn is necessary for the growth of BMHP crystals .The characteristics of well grown crystals are carried out by FTIR, TGA/ DTA, SEM, XRD and etching.